Abordagem de suporte à privacidade em aplicações móveis considerando a expectativa de usuários - Mello, Jose Santiago Moreira de (2018)
Privacy is the cause of an important concern in the context of mobile applications, once these applications manipulate a countless number of the users’ confidential and personal information through their mobile devices. Previous researches have shown that the manipulation of information through the applications is commonly unknown to the user, or, when known, the reason for this collection is not clear enough. Several automated tools have been proposed to analyze the performance of mobile applications regarding their privacy. However, these tools don’t take into consideration the users’ perception about what they believe to be collected and the purpose of this collection. Concerning this, the current work presents an approach for privacy applied in the mobile context, in which people’s expectation of the aspects of collection and the use of information by smartphone applications are considered. This study shows the results of a research performed with 163 smartphone users which was used as a basic resource to understand how people’s expectations may impact their subjective feelings (levels of comfort). WePrivacy service is also presented, mainly composed of a mobile application, a concept which implements the idea of privacy and responds the question of research discussed in this work, that is, how to consider people’s expectation in the evaluation and support to the decision making on privacy in the use of mobile applications. The results found suggest that the users don’t know how to point which of their personal information are collected and to which purpose the collection serves. The results also show that when the purposes of the collection are known, the users tend to feel more comfortable.